Karakterisasi Sifat Fisikokimia dan Fungsional Terigu Modifikasi Panas - Lena Nur Aulana; Sugiyono Sugiyono; Elvira Syamsir (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2015)
Based on the availability of water, heat treatment modifications of wheat flour can be classified into two basic methods, they are dry and wet heating modifications. The different methods would influence the characteristics and the suitable application of the flour. The objective of this research was to characterize the physicochemical and functional properties of dry and wet heating-treated wheat flours. Heat treated wheat flour had lower moisture content compared to untreated flour. The moisture content of dry heated flour was lower than wet heated flour, while the protein content of dry and wet heated wheat flour had no significant difference. Functional characteristics of wet heated wheat flour on water absorption parameter gave the highest value than dry heated and untreated flour. Gluten index of wet heated wheat flour was lower than dry heated and untreated flour. Granular microscopic view showed that heated wheat flour still had birefringence property, while dry heated flour had even more granular birefringence than wet heated flour. According to the pasting properties, heat treated wheat flour showed higher stability and higher ability to bind water than untreated flour, this characteristics was suitable to be used in products that needs water retention and freeze thaw stability.